Effect of Methylation Status of lncRNA-MALAT1 and MicroRNA-146a on Pulmonary Function and Expression Level of COX2 in Patients With Chronic Obstructive Pulmonary Disease - Sun, Li; Xu, Aiqun; Li, Min; Xia, Xingyuan; Li, Pulin; Han, Rui; Fei, Guanghe; Zhou, Sijing; Wang, Ran (Frontiers in Cell and Developmental Biology, 2021)
This study aimed to investigate the role of methylation of MALAT1 and miR-146a in the pathogenesis of chronic obstructive pulmonary disease (COPD). COPD patients were grouped according to their methylation status of MALAT1 and miR-146a promoters and we found that FVC, FEV1 and DLCO were the highest in the MALAT1 HYPO + miR-146a HYPER group and lowest in the MALAT1 HYPER + miR-146a HYPO group. And COPD patients with hypermethylated MALAT1 showed lower expression of MALAT1 than that in the COPD patients with hypomethylated MALAT1. Meanwhile, miR-146a was the most significantly upregulated in the MALAT1 HYPER + miR-146a HYPO group and most significantly down-regulated in the MALAT1 HYPO + miR-146a HYPER group. Both PGE1 and COX2 expression were the highest in the MALAT1 HYPO + miR-146a HYPER group and the lowest in the MALAT1 HYPER + miR-146a HYPO group. In conclusion, our results established a MALAT1/miR-146a/COX2 signaling axis. The overexpression of MALAT1 could increase the expression of COX2 by inhibiting the expression of miR-146a, thus affecting the pulmonary function of COPD patients.